Simian Virus 40 Large T Antigen and Two Independent T-Antigen Segments Sensitize Cells to Apoptosis following Genotoxic Damage - Cole, Sara L. (American Society for Microbiology, 2002)
The simian virus 40 (SV40) large tumor (T) antigen is sufficient to transform cells in cultures and induce tumors in experimental animals. Transformation of primary cells in cultures requires both overcoming growth arrest by stimulating the cell cycle and blocking cell death activities presumably activated by oncogene-mediated hyperproliferation signals. The study presented here examined the ability of specific regions and activities of T antigen to modulate apoptosis in cells treated with the genotoxic agent 5-fluorouracil (5-FU). The results showed that the expression of full-length T antigen rendered rat embryo fibroblasts (REF) sensitive to 5-FU-induced apoptosis. Thus, neither the p53-binding region nor the Bcl-2 homology region of T antigen was sufficient to prevent cell death induced by the DNA-damaging agent. T-antigen-mediated sensitization occurred independently of retinoblastoma protein or p53 and p300 binding. An N-terminal segment containing the first 127 T-antigen amino acids (T1-127) was sufficient to sensitize cells. A C-terminal segment consisting of T-antigen amino acids 251 to 708 (T251-708) also sensitized cells to 5-FU-induced apoptosis. This sensitization did not occur when T251-708 was targeted to the nucleus by inclusion of the SV40 nuclear localization signal. The introduction of mutations into the T-antigen J domain resulted in mutation-specific and variable inhibition of apoptosis. This result suggested that either the structural or the functional integrity of the J domain is required to sensitize cells to apoptosis. Treatment of REF or REF expressing full-length T antigen, an N-terminal segment, or T251-708 resulted in increased expression of the p53-responsive MDM2 gene; apoptosis occurred through a p53-dependent pathway, as p53-null cells expressing these T antigens were resistant to 5-FU-induced apoptosis. Possible mechanisms involved in sensitizing cells to a p53-dependent apoptosis pathway in spite of the ability of T antigen to bind and inactivate the transcriptional transactivating activity of p53 are discussed.